Design and Optimization of Cyproheptadine Hydrochloride Fastdissolving Tablet Using Design of Experiment (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The aim of the current research project was to formulate and optimize a fast-dissolving tablet containingthe antihistamine drug cyproheptadine hydrochloride (HCl), which is frequently used to treat allergies and otherconditions. Materials and Methods: The direct compression method was used to prepare the fast-dissolvingtablets of cyproheptadine HCl. Fourier-transform infrared spectroscopy was employed to evaluate the blend’scompatibility and ensure the stability of the active ingredient. The effect of two critical formulation variables:The amount of super-disintegrant (X1) and amount of effervescent agent (X2) – on the dependent variables:disintegration time (DT) (Y1), percentage drug release at 5 min (Y2), and percentage drug release at 10 min (Y3)– was examined using a two-factor, two-level Central Composite Design. Results: Design-Expert® software byStat-Ease 360 trial version 13.0 was used to study the effect of formulation variables on dependent variables.Nine formulations were produced and assessed for several physicochemical characteristics as well as in vitro drugrelease. The data were analyzed using Response Surface Methodology and Analysis of variance. In comparisonto other formulations, the software suggested an optimized formulation (CP OPT) with 5 mg of super-disintegrantand 49.572 mg of effervescent agent with shorter DT and a faster drug release, with over 85% of the drug beingreleased in